HIGH AND DRY IN CENTRAL TIBET DURING THE LATE OLIGOCENE - DeCelles P.G.; Quade J.; Kapp P.; Fan M.; Dettman D.L.; Ding L. (My University, 2007)
The time at which the Tibetan Plateau rose to its present high elevation remains controversial, with estimates ranging from 40 Ma to more recent than 7 Ma. New stable isotope analyses of modern and accurately dated ancient paleosol carbonate in the Nima basin of central Tibet point to an arid climate and high paleoelevation (4.5-5 km, comparable to today's setting) by 26 Ma. Oxygen isotope values of ancient (26 Ma) soil carbonate are both very negative and indistinguishable-after modest corrections for changes in global climate-from the lowest (least evaporated) oxygen isotope values of modern soil carbonates in the area. Substantial enrichments in oxygen-18 in paleolacustrine carbonates, as well as high carbon isotope values from paleosol carbonates, indicate considerable lake evaporation and low soil respiration rates, respectively, and both are consistent with the present arid climate of the Nima area. Blockage of tropical moisture by the Himalaya and perhaps the Gangdese Shan probably has contributed strongly to the aridity and very negative oxygen isotope values of soil carbonate and surface water in the Nima area since at least the Late Oligocene. The maintenance of high elevation since at least 26 Ma suggests that any flow of lower crust from beneath central Tibet must have been balanced by coeval northward insertion of Indian crust beneath the Plateau. © 2006 Elsevier B.V. All rights reserved.
Keywords: CARBON ISOTOPES; CONTINENTAL TECTONICS; OXYGEN ISOTOPES; PALEOELEVATION; TIBET; Oligocene; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен